2016
DOI: 10.1111/codi.13120
|View full text |Cite
|
Sign up to set email alerts
|

Definitive seton management for transsphincteric fistula‐in‐ano: harm or charm?

Abstract: Despite its retrospective non-comparative design, the study has demonstrated that a cutting seton is a safe, well tolerated and highly successful treatment for transsphincteric anal fistula and is followed overall by improved continence. The results compare very favourably with other techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 46 publications
6
15
0
1
Order By: Relevance
“…They reported a healing time of 3.6 weeks which was lower than that analysed in our study probably due to inclusion of both low and high anal fistulas in the former study. Rosen et al 17 reported a healing time of 3 months which was comparably long probably due to increased intervals between progressive tightening of the seton wire (1 month) compared to 1 week in our study.…”
Section: Table 3 Comparison Of Pain Between the Two Groupssupporting
confidence: 44%
“…They reported a healing time of 3.6 weeks which was lower than that analysed in our study probably due to inclusion of both low and high anal fistulas in the former study. Rosen et al 17 reported a healing time of 3 months which was comparably long probably due to increased intervals between progressive tightening of the seton wire (1 month) compared to 1 week in our study.…”
Section: Table 3 Comparison Of Pain Between the Two Groupssupporting
confidence: 44%
“…Anecdotal comparison of ultrasound appearances of the sphincters after cutting seton suggest less sphincter separation than after fistulotomy, but it is uncertain if like is being compared with like [116]. Rosen and Kaiser [117] used data from Ritchie et al [118] to demonstrate an association between the rate of incontinence and the interval between seton tightening, which they interpreted as supporting evidence that slow sphincter division preserves sphincter function. However, this requires a large leap of faith, as the data used were very heterogeneous, with different definitions of incontinence and periods of follow-up.…”
Section: Recommendationsmentioning
confidence: 99%
“…However, follow‐up was short and postoperative assessment of continence was limited. Rosen and Kaiser reported on 121 patients with a transsphincteric fistula treated by tight seton. Initial healing occurred in 90% of patients, rising to 98% after further surgical procedures.…”
Section: Treatmentmentioning
confidence: 99%
“…Hippocrates was the first to use this technique where he inserted horsehair with lint in the fistula tract and then periodically tightened it. It is used almost for all types of anal fistulae and is showing a high healing rate between 80-100% 19,20 . However there is a lot of controversy regarding this type of operation and generally, nowadays it is not anymore recommended for anal fistula treatment because of a relevant incontinence rate in some studies with numbers fluctuating between 0-63% 10,21,22 .…”
mentioning
confidence: 99%